Effect of Values and Business Ethics Course on Students’ Perception of Ethics in Business: An Empirical Investigation of Management Students in Tripura - Das, Manish (Prabandhan: Indian Journal of Management, 2015)
This study investigates the changes in perception level of students regarding the values and ethics taught in the professional MBA program. Students of the management department of a University in Tripura were taken into consideration for the purpose of conducting the study. The students of the university (for three consecutive batches, that is, 2009-11,2010- 12,2011-13) were asked to fill up their opinion regarding some close-ended statements at the beginning of the respective semester in which business ethics is taught as a subject, and their opinion was also sought after the course had been taught. The study used paired sample t - test for the analysis of the opinion of the students. This study concludes that after getting exposure to the business ethics course, the perception levels of students pertaining to analyzing statements related to values and business ethics came down significantly.